Analisis terjadinya hentakan dan suara keras pada suspensi belakang unit dump truck HD 785-7 - Hendro Purwono; Rasma Rasma; Riki Effendi (TURBO [Tulisan Riset Berbasis Online], 2019)
The suspension system on the machine unit is very important to support the unit weight against the road surface and also protect the transmission from the vertical vibration of the wheels to the body of the unit. When the unit passes a damaged or bumpy road at high speed, shock loads from the road surface will be felt, so the role of the suspension is crucial in protecting components from damage, maintaining operator comfort and undamaged loads. HD 785-7 unit is one type of dump truck that uses cylindrical pneumatic hydro suspension that contains nitrogen and oil gases to absorb loads or vibrations from the road surface. In its operation which functions as a material carrier in the mine area, there are often problems with the suspension especially at the rear because it is holding a heavier load. Therefore, research needs to be carried out aimed at finding the main causes and solutions to these problems using data collection methods, namely: field surveys, interviews, and library research. The results show that damage to the valve core causes the valve to leak and cause the chamber at the top of the cylinder suspension to be occupied by nitrogen gas to be reduced so that the suspension suffers harsh strokes when operated especially on damaged roads. Damage to the valve core is caused by the use of non-standard and too tight tools in its installation. Keywords: hard suspension, valve core, feed valve, nitrogen gas, oil.